2007
DOI: 10.1159/000098546
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Bone Health in Adolescent Elite Rhythmic Gymnasts despite Hypoleptinemia

Abstract: Background/ Aims: Leptin is linked to hormonal disturbances occurring in anorexia and positively linked with bone mineral density. The aim of this study was to determine whether hypoleptinemia occurring in rhythmic gymnasts may affect bone health. Method: Leptin, insulin, cortisol, IGF1 levels and bone markers were determined in 36 rhythmic gymnasts (EG) and 20 controls (C). Body composition, BMD at the whole body (WBBMD), lumbar spine (LSBMD) and bone ultrasound properties (SOS, BUA) were measured. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 62 publications
1
39
0
1
Order By: Relevance
“…In this study, we confirmed the delayed age of menarche (mean age: 14 vs 12.6 years in the French population) (27) and the high prevalence of menstrual disorders. Conversely, no alteration in either peak bone mass acquisition or the IGF1/IGFBP3 ratio was observed, in agreement with previous reports (12,22). The multivariate analysis suggested that the plasma E 2 level may not be a strong determinant of BMD acquisition, except at the lumbar spine, a trabecular bone site that is more sensitive to estrogen deficiency (28).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we confirmed the delayed age of menarche (mean age: 14 vs 12.6 years in the French population) (27) and the high prevalence of menstrual disorders. Conversely, no alteration in either peak bone mass acquisition or the IGF1/IGFBP3 ratio was observed, in agreement with previous reports (12,22). The multivariate analysis suggested that the plasma E 2 level may not be a strong determinant of BMD acquisition, except at the lumbar spine, a trabecular bone site that is more sensitive to estrogen deficiency (28).…”
Section: Discussionsupporting
confidence: 90%
“…Although a concomitant increase in BMD and leptin concentration has generally been observed during growth (8), the implication of leptin in bone mass accretion remains questionable in both young athletes (6,22,33) and controls (8,10). In our earlier cross-sectional study, we reported that the basal leptin level was not an independent predictor of BMD (7).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This idea of leptin as an insulin-sensitizing hormone and leptin deficiency, or resistance, as a potential link between obesity and diabetes has been reviewed recently (Yildiz, 2006). The plasma leptin level has a direct relation with the fat tissue and a negative relation with the body fitness or physical activity (Courteix et al, 2007). Physiological stress resulting from physical activity is one of the potential regulators of leptin secretion from adipose tissue.…”
Section: Introductionmentioning
confidence: 99%